(untitled) (Dhaka University Journal of Science, 2020)
With the aim of determining stability constants of iron(II) complexes of 3-(2-pyridyl)-5,6-diphenyl-1,2,4-triazine (PDT), 3-(2-pyridyl)-5,6-bis(p-methoxyphenyl)-1,2,4-triazine (PBMPT) and 3-(2-pyridyl)-5,6-bis(4-biphenyl)-1,2,4-triazine (PBBT), these organic reagents were prepared from commercially available relatively cheaper reactants. The absorptiometric characteristics of iron(II) complexes of these organic compounds; λmax and molar absorptivity (€max) were determined. The composition and stability constants of these iron(II) complexes were determined by both molar ratio and Job’s continuous variation methods. The mean logK values for iron(II) complexes of PDT, PBMPT and PBBT were found 16.48, 17.48 and 15.54 respectively reflecting the formation of very stable complexes. These are well comparable with the reported values for the iron(II) complexes of 2,2’-bipyridine, 1,10- phenanthroline, Ferrozine and Ferene. Higher sensitivity and stability constant values reflects the possibility of application of these compounds as promising chromogenic reagents for iron determination. Dhaka Univ. J. Sci. 68(2): 137-142, 2020 (July)